The global effects of widespread adoption of climate smart agriculture - De Pinto, Alessandro (2018)
Climate Smart Agriculture (CSA) is a relatively new approach to agricultural development that aims at increasing productivity in the agricultural sector under changing climate regimes while reducing greenhouse gas (GHG) emissions. We perform an ex-ante assessment of the effects of widespread adoption of CSA by linking spatially-disaggregated data from three different models and focus on three crops, maize, wheat, and rice, which represent about 41% of the global harvested area and 64 % of GHG emissions generated by crop production. The impact of adoption of selected CSA practices is evaluated against a plausible business-as-usual scenario for the period 2010 – 2050 under two climate change scenarios. We find that the highest possible impact of the CSA practices considered is to increase global maize and wheat production by about 4%, and global rice production by 9%. These changes lead to a decrease in the number of people at risk of hunger estimated to be between 23 and 40 million worldwide. Average annual reduction of GHG emissions ranges between 44 and 101 Mt CO2 e. While substantial, this reduction is only 4 – 10% of the estimated global reduction in emissions from the agricultural sector necessary to remain below a 2 °C warming.